As contribuições do Grupo Doce Melodia através do ensino coletivo de instrumento musical: o caso dos estudantes do ensino fundamental da EEIF Constância de Sousa Muniz. - Carvalho, Maria do Livramento (2018)
This research, accomplished in the public school Constancia de Sousa Muniz, located in Cruz (Ceará), presents the contributions of the methodology of Collective Teaching of Musical Instrument (CTMI) in school development of the students, based on the musical practice experienced in the Doce Melodia group. The main objective of this research is to investigate the influences of the CTMI practice within the group Doce Melodia, observing its contributions on the participants‟ development, observing contributions concerning to their interest and school performance in the school context. Seeking to confirm the hypothesis that the CTMI influences school development on participants of Doce Melodia group, we will use references about this teaching methodology, in order to get knowledge about its use and its benefits. It is a qualitative research, whose method is the case study, in which the data were collected through a questionnaire applied with teachers of regular education in the classes of 4th and 5thgrades whose studentswere involved on the group, as well as a questionnaire and an interview with thosestudents. In terms of analysis and interpretation of the data collected in this research, it was possible to understand the influences that the musical practice using the methodology of the Collective Teachinghad in the group DoceMelodia and offered to the school development of the participant students.